Impact of solid second phases on deformation mechanisms of naturally deformed salt rocks (Kuh-e-Namak, Dashti, Iran) and rheological stratification of the Hormuz Salt Formation. (May 2015) - Závada, P.; Desbois, G.; Urai, J.L.; Schulmann, K.; Rahmati, M.; Lexa, O.; Wollenberg, U.
Abstract: Viscosity contrasts displayed in flow structures of a mountain namakier (Kuh-e-Namak - Dashti), between 'weak' second phase bearing rock salt and 'strong' pure rock salt types are studied for deformation mechanisms using detailed quantitative microstructural study. While the solid inclusions rich ("dirty") rock salts contain disaggregated siltstone and dolomite interlayers, "clean" salts reveal microscopic hematite and remnants of abundant fluid inclusions in non-recrystallized cores of porphyroclasts. Although the flow in both, the recrystallized "dirty" and "clean" salt types is accommodated by combined mechanisms of pressure-solution creep (PS), grain boundary sliding (GBS), transgranular microcracking and dislocation creep accommodated grain boundary migration (GBM), their viscosity contrasts observed in the field outcrops are explained by: 1) enhanced ductility of "dirty" salts due to increased diffusion rates along the solid inclusion-halite contacts than along halite–halite contacts, and 2) slow rates of intergranular diffusion due to dissolved iron and inhibited dislocation creep due to hematite inclusions for "clean" salt types Rheological contrasts inferred by microstructural analysis between both salt rock classes apply in general for the "dirty" salt forming Lower Hormuz and the "clean" salt forming the Upper Hormuz of the Hormuz Formation and imply strain rate gradients or decoupling along horizons of mobilized salt types of different composition and microstructure. Highlights: Solid inclusions in the "dirty" Hormuz rock salts promote the solution-precipitation creep. Solid inclusion rich rock salts of Lower Hormuz are weaker in flow than equivalent solid inclusion poor rock salts of Upper Hormuz. Flow in Hormuz rock salts is accommodated by solution-precipitation creep and dynamic recrystallization coupled with transgranular microcracking. Flow of "clean" rock salts is inhibited by decreased inter-granular diffusion rates due to dissolved Fe 3+ .